2002
DOI: 10.1080/003655202762671279
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Accommodation of Proximal Stomach in Patients with Alcoholic Liver Cirrhosis

Abstract: This study reveals an impairment of the proximal stomach in alcoholic cirrhotic patients. The low calorie liquid meal distinguishes between the two groups of cirrhotic patients and healthy controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 44 publications
0
16
1
2
Order By: Relevance
“…In a previous ultrasonographic study, reduced relaxation of the proximal stomach after a meal was reported in patients with alcoholic liver cirrhosis compared to healthy controls [61]. However, ongoing alcohol overconsumption was not mentioned as an exclusion criterion in this study [61].…”
Section: Gastric Sensorimotor Dysfunction (Ii)mentioning
confidence: 73%
See 3 more Smart Citations
“…In a previous ultrasonographic study, reduced relaxation of the proximal stomach after a meal was reported in patients with alcoholic liver cirrhosis compared to healthy controls [61]. However, ongoing alcohol overconsumption was not mentioned as an exclusion criterion in this study [61].…”
Section: Gastric Sensorimotor Dysfunction (Ii)mentioning
confidence: 73%
“…However, ongoing alcohol overconsumption was not mentioned as an exclusion criterion in this study [61]. Acute and chronic alcohol consumption have been associated with altered motility in the esophagus, stomach, and the small intestine [165,166].…”
Section: Gastric Sensorimotor Dysfunction (Ii)mentioning
confidence: 98%
See 2 more Smart Citations
“…Anorexia, nausea, encephalopathy, gastropathy, ascites, and concurrent alcohol consumption can all contribute to a reduction in dietary intake (6). Malabsorption and maldigestion of nutrients can also result from bile salts deficiency, altered intestinal motility, bacterial overgrowth, mucosal injury, portal hypertensive changes to the intestine, and increased intestinal permeability (7)(8)(9). Apart from the abovementioned established factors, myths and fads about diet related to liver diseases in countries like Pakistan further contributes to the problem.…”
Section: Introductionmentioning
confidence: 99%